A Stiffness-Fault-Tolerant Control Strategy for a Redundant Elastic Actuator - Velasco Guillen, Rodrigo Jose; Furnemont, Raphael; Verstraten, Tom; Beckerle, Philipp (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, AIM, 2022)
Elastic actuators show advantages in energy efficiency and safety in human-robot interaction. However, such actuators might be subject to faults due to their complexity, particularly in elastic and kinematic elements. We present a stiffness-fault-tolerant control strategy for a redundant actuator with multiple elastic actuation units. The control scheme is capable of detecting and compensating for stiffness changes in individual elastic elements. We develop the dynamics of the actuator and a model-based impedance control scheme. The obtained closed-loop dynamic interaction behavior of the system and its stability is analyzed. Oscillatory trajectory simulations are used to evaluate the control strategy. Results show that the controller is capable of tracking a reference trajectory with desired interaction impedance behavior under fault conditions and interaction disturbances, while exploiting redundancy to perform load compensation.
CRIS-Team Scopus Importer:2022-09-30